Drying rate and thermal properties of solid fuel produced from hydrothermal and vapourthermal carbonization of high moisture content biomass material - Jaafar, Muhammad Afiq (Universiti Sains Malaysia, 2017)
Energy improvement of high moisture content biomass material can be done by using water (in HTC) and saturated steam (VTC) as reaction medium, which reduces the necessity for drying process thus reducing energy consumption. At present, there are a few drying rate analysis on both HTM and VTM. This particular project goal is to determine the influence of water-to-biomass ratio on drying rate in term of energy consumption and other properties of torrefied product of HTM, and to compare it with VTM. Besides, the properties of torrefied product was measured and analysed which affect the quality of HTM and VTM. The temperature and pressure of 220oC and 24 Bar respectively were used for VTM and HTM and fixed for each process. The manipulated parameter of this experiment were the type of biomass used which was bagasse and lime peel and vary on water-to-biomass ratio. Thermogravimetric and bomb calorimeter analysis was done to determined and prove the quality of HTM and VTM. The result show that VTM has the lowest drying rate and rapidly dried compared to HTM while the raw material has the lowest drying rate. HTM with the lowest water-to-biomass ratio (highest weight of biomass) has the highest drying rate. Moreover, the lime Peel and bagasse HTM with ratio water-to-biomass of 52.3:1 and 34:1 are the most quality among HTM for each sample with HHV 18.301Mj/Kg and 18.314 Mj/Kg. Besides that, the fixed carbon of raw material for lime peel and bagasse sample was increase from 2.259%-10.538% and 0.106%-13.428% respectively. However, VTM was dominated for the most quality torrefied material for both lime peel and bagasse with HHV of 20.957 Mj/Kg and 20.041 Mj/Kg respectively. This study demonstrate determining the correct water-to-biomass ratio is crucial in determining quality of HTM.